Toward European harmonization of national myasthenia gravis registries: modified Delphi procedure-based expert consensus on collectable data - Slioui, Abderhmane; Tammam, Giulia; Vanoli, Fiammetta; Marina, Adela Della; Vohanka, Stanislav; Gilhus, Nils Erik; Moroni, Isabella; Leite, Maria Isabel; Piehl, Fredrik; Antozzi, Carlo; Pini, Jonathan; Stascheit, Frauke; et al. (Orphanet journal of rare diseases, 2025)
BACKGROUND: Myasthenia gravis (MG) is a rare autoimmune disorder. Several new treatment concepts have emerged in recent years, but access to these treatments varies due to differing national reimbursement regulations, leading to disparities across Europe. This highlights the need for high-quality data collection by stakeholders to establish MG registries. A European MG registry could help bridge the treatment access gap across different countries, offering critical data to support regulatory decisions, foster international collaborations, and enhance clinical and epidemiological research. Several national MG registries already exist or are in development. To avoid duplication and ensure harmonization in data collection, a modified Delphi procedure was implemented to identify essential data elements for inclusion in national registries. RESULTS: Following a literature review, consultations with patient associations and pharmaceutical companies, and input from multiple European MG experts, 100 data elements were identified. Of these, 62 reached consensus for inclusion and classification, while only 1 item was agreed for exclusion. 30 items failed to reach the ≥ 80% agreement threshold and were excluded. Among the 62 accepted items, 21 were classified as mandatory data elements, 32 optional, and 9 items pertained to the informed consent form. CONCLUSIONS: Through a modified Delphi procedure, consensus was successfully achieved. This consensus-based approach represents a crucial step toward harmonizing MG registries across Europe. The resulting dataset will facilitate the sharing of knowledge and enhance European collaborations. Furthermore, the harmonized data may assist in regulatory or reimbursement decisions regarding novel therapies, as well as address treatment access disparities between European countries.
Keywords: delfská metoda; Registries; sběr dat; Humans; Consensus; registrace; European registry; lidé; myasthenia gravis; Myasthenia gravis; Europe; Data Collection; mezinárodní spolupráce; International Cooperation; konsensus; Delphi procedure; Expert panel; Rare disease registry; Myasthenia Gravis; Delphi Technique; Evropa